2005
DOI: 10.1007/s00296-005-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold videocapillaroscopy in patients with systemic lupus erythematosus

Abstract: Nailfold videocapillaroscopy was performed in 21 controls (C) and 21 patients (P) with systemic lupus erythematosus (SLE) classified according to the American College of Rheumatology, with, at least, 1 year of diagnosed disease and having low activity (MEX-SLEDAI) and sequel (SLICC) indexes at the time of the examination, paired by sex and age. Red blood cell velocity (RBCV, mm/s) at rest and after the release of 60s arterial occlusion (RBCVmax, mm/s), time to reach it (TRBCVmax, s), functional capillary densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…Prevalence of MS is also high in lupus erythomatosus, where it amounts to 18% [ 249 ]. However, a study on microcirculation in vivo could not find morphological or functional defects in capillary parameters [ 74 ]. Finally, one should mention the multiorgan IR observed in human immunodeficiency virus (HIV) infected patients, where insulin sensitivity correlates positively with adiponectin levels and negatively with IL‐6 [ 324 ].…”
Section: Metabolic Syndrome: a Condition Present In Many Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of MS is also high in lupus erythomatosus, where it amounts to 18% [ 249 ]. However, a study on microcirculation in vivo could not find morphological or functional defects in capillary parameters [ 74 ]. Finally, one should mention the multiorgan IR observed in human immunodeficiency virus (HIV) infected patients, where insulin sensitivity correlates positively with adiponectin levels and negatively with IL‐6 [ 324 ].…”
Section: Metabolic Syndrome: a Condition Present In Many Diseasesmentioning
confidence: 99%
“…Interestingly, data about CD are strongly divergent among the various diseases expressing MS. No changes were seen in low birth weight [ 133 , 179 , 404 ], insulin‐resistant fructose‐fed rats [ 397 ], lupus [ 74 ], and hypothyroidism [ 363 ]. In acromegaly, divergent reports exist, two studies showing no change [ 14 , 344 ] and one showing reduced number of capillaries and length as well as increased tortuosity even in normotensive patients [ 351 ].…”
Section: Microcirculation In States Of Metabolic Syndromementioning
confidence: 99%
“…Edema may represent trauma, especially in children, but it is not specific and is also reported in other pathologies, such as diabetes. [27][28][29] We found edema in all ages and none of our patients indicated previous trauma. Trauma in children is more common than in other ages and may not be reported correctly as such by the child, whereas adolescents and adults may inform if there was any trauma event.…”
Section: Discussionmentioning
confidence: 50%
“…Dancour et al 28 found statistical difference in capillary diameter between 21 SLE patients and 21 controls.…”
Section: Resultsmentioning
confidence: 99%